2010
DOI: 10.1590/s1516-18462010005000051
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de perda auditiva e fatores associados na população idosa de Londrina, Paraná: estudo preliminar

Abstract: OBJETIVO: estimar a prevalência de Perda Auditiva (PA), identificando os fatores associados em pacientes idosos de Londrina - PR. MÉTODOS: estudo transversal realizado em amostra populacional de 61 indivíduos com idade igual ou superior a 60 anos, em 2009, através de anamnese e avaliação audiológica. Aplicou-se o teste do Qui-quadrado e o do Risco Relativo com 95% de confiança e valor de p<0,05 para as análises univariadas entre PA e fatores associados. RESULTADOS: de toda a amostra 87,70% apresentaram algu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
20
0
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 18 publications
4
20
0
10
Order By: Relevance
“…Other studies (11,12,20) also found as common complaints regarding tinnitus, dizziness, otalgia and pruritus. Regarding general health condition, the main disease referred by elderly were high blood pressure (51.43%), similar to other studies involving elderly populations (11,21,22) . Various subjects in this survey reported noise exposure.…”
Section: Discussionsupporting
confidence: 87%
“…Other studies (11,12,20) also found as common complaints regarding tinnitus, dizziness, otalgia and pruritus. Regarding general health condition, the main disease referred by elderly were high blood pressure (51.43%), similar to other studies involving elderly populations (11,21,22) . Various subjects in this survey reported noise exposure.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, more than 70% of the sample exhibited mild-to-moderate hearing loss (Table 4), with a mild downward sloping configuration in both groups (Table 3). These findings corroborate the results of other studies that investigated hearing in older adults 10,23,24,29 . As presbycusis is associated with aging, being caused by auditory degeneration of the basal portion of the cochlea 12,24 , the predominance of sensorineural hearing loss attended by gradual affection of the audibility thresholds was expected, as the high frequencies are the most severely affected in presbycusis.…”
supporting
confidence: 91%
“…In population-based survey -conducted among 238 senior in Rio de Janeiro city -it was identified a prevalence of hearing loss (measured by audiometry) in 42.9% of the women and in 64.3% of the men 22 . Among the 343 seniors of a population survey in Londrina (Paraná, a southern Brazilian state), there was a prevalence of hearing loss or lowering frequencies at 87.7% 23 . We consider hearing self-assessment a possibly useful hearing health indicator, and we do recommend its use in epidemiological studies in case audiometry -taken as a golden standard test 24 -is impracticable.…”
Section: Discussionmentioning
confidence: 99%